STUDI KOMPARASI KEPENGAWASAN DALAM IMPLEMENTASI K13 DI SDN 08 KEPAHIANG DAN MIN 01 KEPAHIANG - Jeki Pausan (IAIN Bengkulu, 2016)
This study aims: 1) To determine the role of supervisor preformance aspects of preparation on the teachertraining curriculum at MIN 01 Kepahiang with 08 Kepahiang Elementary School 13, 2) To determine the role of supervisorsin overseeing the implementation of teacher learning in the curriculum 13 at MIN 01 Kepahiang the Primary School08 Kepahiang 3) to determine the ratio of school supervisors of the implementation of the curriculum in 2013 at MIN01 Kepahiang with SDN 08 Kepahiang. Data collection techniques used in this study were interviews, observation anddocumentation. While the results of this study concluded on supervisory Comparative Studies in Implementation K 13at SDN 08 MIN 01 Kepahiang Kepahiang and authors to conclude that: 1. The role of watchdog preformance aspectsof preparation on the teacher training curriculum at MIN 13 01 Kepahiang with 08 elementary schools Kepahiang Thatdid training to teachers in making tools completeness of teachers in the teaching and learning process diruang class, inorder to avoid errors due to the curriculum in 2013 included something new. 2. The role of supervisors in overseeing theimplementation of teacher learning in the curriculum 13 at MIN 01 Kepahiang with 08 Kepahiang Elementary Schoolis to supervise when the teacher teaches, check the complete instrument to teach and evaluate the activities of teachersin teaching. 3. a. There is a difference of Trustees work in SDN 08 Kepahiang to MIN 01 Kepahiang, Superintendent atSDN 08 Kepahiang with Kepahiang 01 MIN. a. Supervision at SDN 08 Kepahiang, namely: 1). Trustees of the Diasporahave the obligation overseen many as 14 schools. b. Trustees of Dispora overseen teachers who teach general subjects,c. Trustees of the Diaspora in the lift and dismissed by the Ministry of Education and Sports. 3.B. Supervisory MIN 01Kepahiang, namely: 1). If the Supervisory Madrasah has the burden or the amount meant to oversee school is 7., 2).Supervisory MIN 01 Kepahiang supervise teachers who teach subjects which particular religion, 3) Supervisory MIN 01Kepahiang appointed and dismissed by the Ministry of Religious Affairs